Plasma levels of polychlorinated biphenyls (PCB) and the risk of soft tissue sarcoma: PCB and soft tissue sarcoma risk - Guercio, Valentina; Donato, Francesca; Pelucchi, Claudio; Verga, Federica; Passini, Valter; Galeone, Carlotta; Negri, Eva; Garzaro, Giacomo; Boffetta, Paolo; La Vecchia, Carlo; Tavani, Alessandra; Pira, Enrico (La Medicina del Lavoro, 2019)
Background: Soft tissue sarcoma (STS) is a heterogeneous group of rare neoplasms whose aetiology is largely unknown. Dioxin and dioxin-like compounds, including 2,3,7,8-tetrachlorodibenzo-p-dioxin (2,3,7,8-TCDD) and polychlorinated biphenyls (PCBs), are potential risk factors for STS. Objectives: To investigate the relation of 17 PCBs congeners, assessed in human plasma, with STS risk. Methods: We conducted a case-control study in Italy, including 52 STS cases and 99 hospital-based controls. Selected PCB were extracted by high-performance liquid chromatography (HPLC) and measured with gas chromatography-mass spectrometry (GC-MS). Odds ratios (OR), and the corresponding 95% confidence intervals (CI), were estimated through multivariate logistic regression models. Results: The most frequently detected PCB congeners were 138, 170, 180 and 149 (detected in 40-77% of controls). The OR for the sum of all 17 PCB congeners was 1.20 (95% CI 0.50-2.92). In categorical analysis no consistent association was found for individual congeners and for groups based on Wolff’s classification or the degree of chlorination. For continuous estimates, borderline positive associations emerged for Wolff’s groups 2A (OR 1.23, 95% CI 0.97-1.55), 2B (OR 1.34, 95% CI 1.00-1.77, and 3 (OR 1.19, 95% CI 0.96-1.49), for moderately (OR 1.20, 95% CI 0.96-1.51) and highly (OR 1.18, 95% CI 0.99-1.41) chlorinated PCBs, and for congeners 170 (OR 1.26, 95% CI 0.98-1.63), 180 (OR 1.26, 95% CI 0.97-1.64) and 138 (OR 1.45, 95% CI 1.02-2.04). Discussion: Most associations between PCBs and STS risk were not significant, but, given the limited sample size, we cannot exclude moderate associations.